Analysis of Student Opinions on the Motivation of Physical Education Lessons (GYMNASIUM, 2019)
The motivation assessment regarding the attendance of physical education classes was known by the survey of 652 students from the secondary school, 345 boys and 306 girls. We used the motivation study survey, where the questionnaire contained 9 questions regarding the activity within the physical education classes and 3 questions containing information about the students. After investigating the students we can say that most are motivated to come to school, participate actively in physical education, are not happy if the lesson is canceled, over 50% sometimes talk to parents about the activity, they do not want another teacher at class, he practices different sports, especially handball and football, besides they want to introduce tennis, and he does not attend physical education and sports classes to diminish the general success or avoid absences.
Keywords: students; lesson; inquiry; motivation